1987
DOI: 10.1007/bf02734941
|View full text |Cite
|
Sign up to set email alerts
|

Раэделяемые Раэложения Для Релятивистских Многоканальных Проблем Рассеяния

Abstract: A new approach to the multichannel scattering problem with realistic local or nonlocal interactions is developed. By employing the negative-energy solutions of uncoupled Sturmian eigenvalue problems referring to simple auxiliary potentials, the coupling interactions appearing in the original multichannel problem are approximated by finite-rank potentials. By resorting to integral-equation techniques the coupled-channel equations are then reduced to linear algebraic equations which can be straightforwardly solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The diagonalizing matrix Q then can be chosen orthogonal, with the Γ × N 1 eigenvalues η (1) p being purely real quantities. Then, a completeness relation [4,5,6] for the potential V cc ′ can be established, namely…”
Section: A Sturmian Expansion Of a Multichannel Interactionmentioning
confidence: 99%
See 2 more Smart Citations
“…The diagonalizing matrix Q then can be chosen orthogonal, with the Γ × N 1 eigenvalues η (1) p being purely real quantities. Then, a completeness relation [4,5,6] for the potential V cc ′ can be established, namely…”
Section: A Sturmian Expansion Of a Multichannel Interactionmentioning
confidence: 99%
“…have been discussed in detail elsewhere [4,5,6,7,8]. With Φ cn (r), the Weinberg (or sturmian) functions in coordinate space, those form factors then are given by…”
Section: A Sturmian Expansion Of a Multichannel Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…The model, though simple, has very general features. In particular, the restriction to multirank interactions is no limitation, since it has been demonstrated that any interaction can be reduced to a multirank one by the Sturrnian expansion [7] or as in the work of the Gratz group [8].…”
Section: Introductionmentioning
confidence: 99%
“…Negative-energy Weinberg states (NEWS) have been similarly used with good success for generating a separable representation of the two-body T matrix for many years [7]. Renewed activity with NEWS has more recently provided a separable representation for the T matrix for modern potentials [8], and also for obtaining the energy dependence of the dynamic polarization potential due to channel coupling at the threshold of the opening of a new channel [9]. NEWS are also used in atomic scattering situations [10],or for including the efFects of breakup in deuteron-nucleus transfer reactions [11].…”
Section: Intrc)ductionmentioning
confidence: 99%